Analisis Analisis Yuridis Tentang Proses Mediasi dalam Alternatif Penyelesaian Sengketa Tanah Adat di Bali: Indonesia - I Dewa Ayu Dwi Mayasari; Dewa Gde Rudy (Kertha Wicaksana, 2021)
Nowadays in community life there are often conflicts or disputes. Including land disputes that are rife in indigenous communities, especially indigenous peoples in Bali. Various ways have been used by the community to resolve land disputes that occur. Either through court institutions (litigation) or institutions outside the court (non litigation). Many community members have taken alternative dispute resolution because they are considered more effective and do not take more time and money. One alternative dispute resolution that is often taken is through Mediation or peace. Especially in resolving customary land disputes in Bali. Alternative resolution of customary land disputes in Bali is often pursued through a mediation process because it is considered more effective, does not take long and is high cost. In this study, two issues are discussed, namely how the urgency of mediation as an alternative to resolving customary land disputes in Bali and how the mediation process is in alternative settlement of customary land disputes in Bali. This research uses a type of normative legal research because it focuses on the analysis of legal norms that emerge using a statutory approach and a legal concept analysis approach. Due to the complexity of the issue of customary land in Bali and the lack of written rules regarding it, Mediation as an alternative to resolving customary land disputes in Bali is very urgent because disputes can be resolved effectively and efficiently. And the mediation process is not regulated in statutory regulations, so the mediation process tends to be carried out according to the needs of the disputing parties in accordance with the directions and directions of the mediator.